PENGUASAAN HIRAGANA BENTUK SOKUON DAN YOUON PADA SISWA KELAS XII SMAN 7 PADANG - Kartini, Apriyani; Putri, Meira Anggia (Universitas Negeri Padang, 2020)
AbstractÂ This study discusses the mastery of hiragana sokuon and youon to students class XII SMAN 7 Padang. The purpose of is for describing the mastery of hiragana sokuon and youon to students class XII SMAN 7 Padang. The type of research used in this study is quantitative research with descriptive methods. The population in this study was a students of class XII SMAN 7 Padang, amounting to 68 people. The sample in this study was a students of class XII MIPA I SMA N 7 Padang, amounting to 30 people. Data of this research is the score of students test in mastery of hiragana sokuon and youon. Based on the results of the research conducted it can be concluded that the mastery of hiragana sokuon and youon in general is in the